Content Analysis Journal of "Islamic Financial Researches" - Davoud Rajabzadeh; Reza Golami-Jamkarani (تحقیقات مالی اسلامی (پیوسته))
The purpose of this study is to know the content characteristics of the articles published in the journal of Islamic financial research in order to explain its effects in the Islamic financial literature of Iran. Other goals of this research include examining the subject trends of the articles, the authors' contribution pattern, their gender and education level, the most productive universities, educational and research organizations and institutions, as well as examining the type and method of research used by researchers. In this descriptive research-content analysis, the content analysis of 193 articles in 23 issues of the Islamic Financial Research Journal was done. The findings of the research show that 317 people were involved in writing the articles, of which 88.01% were men and 11.99% were women. Among them, 24.61% are assistant professors, 11.67% are associate professors, about 30.28% are doctoral candidates and the rest are at other scientific levels. Also, 86.53% of the published articles were the result of group work and 13.47% were the result of individual work. In examining the organizational affiliation of the authors, Imam Sadiq University is the most active with 26.18%, and AllamehTabatabai, Tehran and Shahid Beheshti Universities are in the next ranks, and also in terms of subject matter, 24.87% of the articles published in In the field of Islamic banking, 23.32% was in the field of Islamic financing tools, and 15.03% in the field of capital market, and 7.25% in the field of Islamic financial jurisprudence and the rest in other fields. The results show that the process of publishing articles in the field of Islamic financial research has been improved by the journal and Islamic financial literature has found a new place in the research fields.